Venetie van Java: Reinterpreting Kota Lama Semarang from a Historical and Tourism Perspective (1824–2024) - Alexandro Yehezkiel Desta Simanjuntak; Muzakki Bashori (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
During the colonial era, Semarang earned the nickname Venetie van Java as a reflection of the city’s character, which was supported by a network of rivers, canals, and rapidly expanding maritime activities, making it an important center of trade and administration on the northern coast of Java. In this context, Kota Lama served as the core of colonial urban development, shaping Semarang’s spatial structure, economic activities, and historical identity. This study aims to analyze the development of Kota Lama between 1824 and 2024 and to examine the dynamics of its transformation into a cultural heritage-based tourism area using historical methods that include heuristics, source criticism, interpretation, and historiography. The research findings indicate that the demolition of the fort in 1824 marked a turning point in the area’s functional shift from a defensive zone to an open city integrated with the colonial economic system and urban development. Entering the 20th century, the Kota Lama experienced a decline due to shifts in the economic center and the orientation of development policies. However, since the early 21st century, revitalization through a conservation approach based on heritage tourism has successfully revived the area as a cultural heritage space with historical, educational, and economic value, thereby reflecting the sustainable transformation from a colonial fortified city into a cultural tourism destination that is adaptive to the times.